Carbon fiber paper based on composites of carbon and polyacrylonitrile for fuel cell application - Aref Arabsahebi; Parisa Akbarian; Mehdi Kheirmand (Carbon Trends, 2024)
Carbon fiber paper is one of the most important substrates used in the gas diffusion layer of the polymer electrolyte membrane fuel cell. A novel approach to creating carbon fiber paper using polyacrylonitrile compounds was proposed in this study. The technique incorporated varying amounts of carbon materials, including carbon black (Vulcan), graphite powder, and carbon nanotubes. Polyacrylonitrile carbon materials were prepared through the spinning process, followed by oxidative stabilization under an oxygen atmosphere at a temperature range of 160–300 °C as the first step. The pliable material undergoes a conversion process to create a compound or ladder that is non-plastic, which is then stabilized in an N2 atmosphere. The fibers are then pre-carbonized at temperatures ranging from 300 to 600 °C and further carbonized between 600 and 1100 °C. After that, Teflon is added and the resulting fibers are made into sheets during the production process. Finally, physical measurements and electrochemical methods such as: checking the amount of water absorption, scanning electron microscope (SEM), chronopotentiometry, electrochemical impedance spectroscopy, electron resistance of carbon sheet, double layer capacitance, and surface roughness parameter were evaluated. The results indicate that the best performance is related to CP7 carbon paper (with a 30–70 % combination of polyacrylonitrile and carbon black).